1999
DOI: 10.1097/00005650-199910000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Washington State Workers' Compensation Managed Care Pilot Project I

Abstract: Workers treated through managed-care arrangements were less satisfied with their care, but their medical outcomes were similar to those of workers who received traditional FFS care. The current workers' compensation system in Washington State affords injured workers great latitude in choosing providers. If provider choice is substantially restricted by managed care, worker satisfaction is likely to diminish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
2
23
1
Order By: Relevance
“…We found no evidence to suggest that early return to work, observed for managed care patients relative to fee-for-service patients, had any important effect on long-term health or employment outcomes (Kyes, Wickizer, and Franklin, 2001). At two years postinjury, the functional status, level of employment, and wages among managed care and fee-for-service patients were similar.…”
Section: Long-term Follow-up Of Patients Treated In the Mcpmentioning
confidence: 62%
See 2 more Smart Citations
“…We found no evidence to suggest that early return to work, observed for managed care patients relative to fee-for-service patients, had any important effect on long-term health or employment outcomes (Kyes, Wickizer, and Franklin, 2001). At two years postinjury, the functional status, level of employment, and wages among managed care and fee-for-service patients were similar.…”
Section: Long-term Follow-up Of Patients Treated In the Mcpmentioning
confidence: 62%
“…The evaluation found no meaningful differences between managed care and fee-for-service patients in health outcomes (Kyes, Wickizer, Franklin, et al 1999). However, it did find important and statistically significant differences favoring managed care patients (see figure 1) in medical and disability costs (Cheadle, Wickizer, Franklin, et al 1999).…”
Section: Washington State Workers' Compensation Managed Care Pilot Prmentioning
confidence: 91%
See 1 more Smart Citation
“…23 We have described some of the policy studies conducted to date on the health care delivered through the system. Other important studies involving evaluation of a major managed care demonstration initiative, 24 -27 outcome assessment of a multi-year drug-free workplace initiative, 28 evaluation of an ongoing quality improvement initiative, 24,29 and patient satisfaction surveys 30,31 have been conducted and reported elsewhere. Most importantly, we believe that the structural capacity built here has had a long-term beneficial effect on both quality of care and cost.…”
Section: Discussionmentioning
confidence: 99%
“…Even when the network has adequate numbers of qualified providers, patient satisfaction may decline if patients are denied access to providers of their choice. Evaluations of WC managed care plans in Florida, Oregon, and Washington state that use restricted networks found that injured workers are significantly and persistently less satisfied than similar workers in traditional workers' compensation plans, even though treatment outcomes for those in restricted provider networks were similar to those for patients in unrestricted networks (11,4). Dissatisfaction was mainly attributed to a lack of provider choice.…”
Section: Restricted Provider Networkmentioning
confidence: 99%